1999
DOI: 10.1038/sj.leu.2401341
|View full text |Cite
|
Sign up to set email alerts
|

The Wilms’ tumor gene WT1 is a good marker for diagnosis of disease progression of myelodysplastic syndromes

Abstract: The Wilms' tumor gene, WT1, is a tumor marker for leukemic blast cells. The WT1 expression levels were examined for 57 patients with myelodysplastic syndromes (MDS) (refractory anemia (RA), 35; RA with excess of blasts (RAEB) 14; RAEB in transformation (RAEB-t), six; and MDS with fibrosis, two) and 12 patients with acute myeloid leukemia (AML) evolved from MDS. These levels significantly increased in proportion to the disease progression of MDS from RA to overt AML via RAEB and RAEB-t in both bone marrow (BM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 16 publications
4
103
0
2
Order By: Relevance
“…116 In a pediatric case with MDS successful withdrawal of immunosuppression due to an increase of WT1 was described: on day 263 after SCT the patient had an increase of the WT1 gene-expression level in the BM (16 000 copies per mg RNA) and in peripheral blood (3700 copies per mg RNA). Cytogenetics confirmed continuing complete cytogenetic remission (he had a trisomy 8 before SCT), and there was full DC.…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%
“…116 In a pediatric case with MDS successful withdrawal of immunosuppression due to an increase of WT1 was described: on day 263 after SCT the patient had an increase of the WT1 gene-expression level in the BM (16 000 copies per mg RNA) and in peripheral blood (3700 copies per mg RNA). Cytogenetics confirmed continuing complete cytogenetic remission (he had a trisomy 8 before SCT), and there was full DC.…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%
“…8 WT1 expression has been evaluated as a marker for risk stratification and MRD detection in AML. [1][2][3][4][5][11][12][13][14] However, contradictory reports refer to the value of WT1 hyperexpression for monitoring MRD during front-line chemotherapy and after allogeneic stem-cell transplantation. Although many authors describe a strong predictive value, 3,4,9,10,15 these findings could not be confirmed by others.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] WT1 mRNA is reportedly a good clinical marker for disease progression, diagnosis and detection of the minimal residual diseases of myelodysplastic syndromes and leukemia. [9][10][11] Thus, depending on the cells and situations expressing WT1, it displays both anti-oncogenic and oncogenic characters. 12 Despite the fact that the oncogenic functions of WT1 have been well documented, its gene-expression mechanism remains undetermined.…”
Section: Introductionmentioning
confidence: 99%